PEMBANGUNAN DESA-KOTA DI INDONESIA DARI PERSPEKTIF PENGEMBANGAN WILAYAH DAN MIGRASI - Febrian, Ranggi Ade (Universitas Riau, 2016)
The problem of rural-urban inequality can not be separated from the development paradigm that assumes thatconsidered better urban and rural areas are higher or the subordination of urban areas. The problem is growingwith the increasing levels of poverty in Indonesia, which was recorded by the BPS period March 2015 as much as28.59 million (11.22% of the total population of Indonesia) in both urban (10.65 million) and rural (17.94million soul). The poverty rate is increasing 860 thousand inhabitants of 27.73 million people in the period ofSeptember 2014, with details of the number of poor people in urban areas amounted to 10.36 million and 17.37million rural people. This paper attempts to analyze the development of villages and cities in Indonesia from theperspective of regional development and migration. Strategy is needed in rural development the city is by adopt-ing the concept of regional development and migration that it contains substances sustainable development ofboth macro and micro, so the construction of rural cities will be able to run well and in line with the Nawa Citathird Indonesian development of the region penggiran by strengthening areas and villages within the frameworkof the Unitary Republic of Indonesia.